Alcohol and cigarette smoking consumption as genetic proxies for alcohol misuse and nicotine dependence. (1st April 2021) - Sanchez-Roige, Sandra; Cox, Nancy J.; Johnson, Eric O.; Hancock, Dana B.; Davis, Lea K.
Highlights: Cigarettes smoked per day is a good genetic proxy for nicotine dependence. Dissimilar genetic association patterns occur between alcohol use and misuse. Alcohol phenotypes may be more influenced by measurement and ascertainment biases. Abstract: Purpose: To investigate the role of consumption phenotypes as genetic proxies for alcohol misuse and nicotine dependence. Methods: We leveraged GWAS data from well-powered studies of consumption, alcohol misuse, and nicotine dependence phenotypes measured in individuals of European ancestry from the UK Biobank (UKB) and other population-based cohorts (largest total N = 263, 954), and performed genetic correlations within a medical-center cohort, BioVU (N = 66, 915). For alcohol, we used quantitative measures of consumption and misuse via AUDIT from UKB. For smoking, we used cigarettes per day from UKB and non-UKB cohorts comprising the GSCAN consortium, and nicotine dependence via ICD codes from UKB and Fagerström Test for Nicotine Dependence from non-UKB cohorts. Results: In a large phenome-wide association study, we show that smoking consumption and dependence phenotypes show similar strongly negatively associations with a plethora of diseases, whereas alcohol consumption shows patterns of genetic association that diverge from those of alcohol misuse. Conclusions: Our study suggests that cigarette smoking consumption, which can be easily measured in the general population, may be good a genetic proxy for nicotine dependence, whereas alcohol consumption is not a direct genetic proxy of alcohol misuse.